Forest Conservation and Development in India– An Analysis of the Forest Rights Act, 2006 and Its Impact on the Forest System - Sahoo, Prajnee Samedhini; Bang, Sanjay; Sahil, Gurudev (Jurnal Cita Hukum, 2024)
Development of any kind is seen as a destroyer of the environment. Development affects the environment, ecology and climate. However, it is necessary for the progress of human beings and, consequently, any country. This gave rise to the concept of sustainable development. Sustainable development is development which fulfils the needs of the present generation while protecting the environment for the needs of the future generation. In India, there are many laws protecting and safeguarding the environment. Many of those laws provide exceptional circumstances under which the environment can be harmed. Most of the time, it is for the public's development. The Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act, 2006, commonly known as the Forest Rights Act, 2006, recognises the rights of forest dwellers over forest land and forest resources for life, habitation and livelihood. These forest dwellers are required by the Act to conserve the forest. It provides for the management of forest and forest resources for the sustainable use of forest dwellers and, at the same time, the protection of the forest. The Act requires the Gram Sabha to conserve and protect biodiversity, wildlife, and forests. The Act also makes provisions for allocating forest land for development purposes. When the law recognises the right of forest dwellers to reside on forest land, it necessarily follows that development facilities like education, roads and others shall be made available. So, the Act recognises the right of forest dwellers over forests and provides for basic developmental facilities for the use of forest dwellers. This research paper analyses the long-standing conflict between environmental law providing for the conservation of the environment and development. It will critically analyse the Forest Rights Act 2006 provisions on the diversion of forest land and a few Supreme Court of India judgments.